Generation of Uniform Magnetic Field between Face-to-Face HTS Bulk Magnets. (September 2019) - Oka, T; Higa, K; Tsunoda, S; Ogawa, J; Fukui, S; Inoue, N; Miryala, M; Murakami, M; Yokoyama, K; Nakamura, T
Abstract: Aiming to develop the compact nuclear magnetic resonance devices, the authors have been developing the uniform magnetic fields in the space between the face-to-face magnetic poles which contain HTS bulk magnets. The authors deformed the original convex shape of the magnetic field distribution to concave by attaching a ferromagnetic iron plate of 20 mm and 100 mm in diameter on one of the pole surfaces. The magnetic field distribution precisely measured along x-axis changed from concave to convex with increasing distance from the magnetic pole surface, which suggested the presence of magnetically flat region. From the results of mapping on the field uniformity data, we have succeeded in obtaining the field uniformity under 500ppm in the space of 4 x 4 x 0.8 mm 3 when the magnetic poles emitting concave and convex field distributions were settled face-to-face with various gaps 30-70 mm. This performance exceeded the target value of 1, 500ppm which is necessary to detect the NMR signals.